MRS in MS, With and Without Interferon Beta 1a Treatment, to Define the Dynamic Changes of Metabolites in the Brain, and to Monitor Disease Progression - Toprak, Münire Kılınç; Çakir, Banu; Ulu, E.Meltem Kayahan; Arat, Zübeyde (IntechOpen, 2012)
None